Expression of Endothelial NOX5 Alters the Integrity of the Blood-Brain Barrier and Causes Loss of Memory in Aging Mice - Adriana Cortés; Maite Solas; Álvaro Pejenaute; Miguel A. Abellanas; Marcos Garcia-Lacarte; Maria S. Aymerich; Javier Marqués; María J. Ramírez; Guillermo Zalba (MDPI AG, 2021)
Blood-Brain barrier (BBB) disruption is a hallmark of central nervous system (CNS) dysfunction, and oxidative stress is one of the molecular mechanisms that may underlie this process. NADPH oxidases (NOX) are involved in oxidative stress-mediated vascular dysfunction and participate in the pathophysiology of its target organs. The NADPH oxidase 5 (NOX5) isoform is absent in rodents, and although little is known about the role it may play in disrupting the BBB, it has recently been implicated in experimental stroke. Our aim was to investigate the role of NADPH oxidase 5 (NOX5) in promoting vascular alterations and to identify its impact on the cognitive status of aged mice. No differences were detected in the arterial blood pressure or body weight between knock-in mice expressing endothelial NOX5 and the control mice. The Morris water maze test showed memory impairments in the aged knock-in mice expressing NOX5 compared with their control littermates. For assessing the BBB integrity, we studied the protein expression of two tight junction (TJ) proteins: Zonula occludens-1 (ZO-1) and occludin. Compared to the control animals, Aged NOX5 mice exhibited reduced levels of both proteins, demonstrating an alteration of the BBB integrity. Our data indicate that vascular NOX5 may favor behavioral changes with aging through oxidative stress-mediated BBB breakdown.